The Relationship Between Psychological Capital and Employee Performance at PPSDMPU Ministry of Transportation - Maharani, Noor Azizah (Syntax Literate, 2025)
Psychological capital is an individual's psychological ability that is positive in nature to support tasks and responsibilities when working which is shown with seriousness during completing tasks, looking positively at positive or negative events that occur, focusing on future orientation, and being able to face various challenges in each task. Employee performance is a set of actions that employees take in accordance with their duties and responsibilities when working to achieve the agency's vision. This study aims to find out empirically the relationship between psychological capital and employee performance at PPSDMPU of the Ministry of Transportation. The research population was 190 employees at PPSDMPU and a sample of 127 employees, consisting of 57 men and 70 women with an age range of 21 – 61 years (= 36 years), based on simple random sampling techniques. The measurement tools used in this study were the Psychological Capital Scale (32 valid items, = 0.941) and the Employee Performance Scale (18 valid items, = 0.873). The results of data analysis using Spearman's Rho showed a correlation of rs=0.725, p<0.05, meaning that there was a significant positive relationship between psychological capital and employee performance at PPSDMPU. The higher the psychological capital you have, the higher the performance of employees at PPSDMPU